2022
DOI: 10.1021/acscatal.2c00486
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Water Activation for Hydrogen Evolution from Ammonia-Borane Studied at a Single-Particle Level

Abstract: Understanding the plasmon-enhanced water activation mechanism is crucial for improving the catalytic activity for ammonia–borane (AB) dehydrogenation. Here, the water activation process is explored at both single-particle and ensemble levels. Kinetic analysis of AB dehydrogenation on Pt–Au nanorods (NRs), especially kinetic isotope experiments, confirmed that water activation is the rate-determining step. Importantly, the activation of water molecules by energetic charge carriers was clarified by in situ singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…Similarly, Zheng et al. found that the KIE values of 5.20 under light irradiation were larger than the values under darkness once the H 2 O was replaced with D 2 O in ammonia‐borane dehydrogenation reaction catalyzed by Pt−Au nanorods, revealing that the photo‐induced hot electrons contributed to O−H bond activation (Figure 4a) [28] . Also, Ye et al.…”
Section: The Fundamental Aspects Of Kinetic Studies On Photo‐thermo C...mentioning
confidence: 86%
See 3 more Smart Citations
“…Similarly, Zheng et al. found that the KIE values of 5.20 under light irradiation were larger than the values under darkness once the H 2 O was replaced with D 2 O in ammonia‐borane dehydrogenation reaction catalyzed by Pt−Au nanorods, revealing that the photo‐induced hot electrons contributed to O−H bond activation (Figure 4a) [28] . Also, Ye et al.…”
Section: The Fundamental Aspects Of Kinetic Studies On Photo‐thermo C...mentioning
confidence: 86%
“…[27] Similarly, Zheng et al found that the KIE values of 5.20 under light irradiation were larger than the values under darkness once the H 2 O was replaced with D 2 O in ammonia-borane dehydrogenation reaction catalyzed by PtÀ Au nanorods, revealing that the photoinduced hot electrons contributed to OÀ H bond activation (Figure 4a). [28] Also, Ye et al reported that slightly smaller KIE value at 1.59 under darkness was determined on steam methane reforming reaction catalyzed by Rh/TiO 2 with respect to that at 1.69 under light, indicating that light-induced hot carriers resulting from the Rh interband transition can increase the KIE values (Figure 4b). [29] Also, Naldoni et al reported that [24] Copyright 2022 Wiley-VCH.…”
Section: The Kinetic Isotopic Effects (Kie) Measurementmentioning
confidence: 93%
See 2 more Smart Citations
“…Due to the lower coordination number of interface atoms compared with surface atoms, the interface usually acts as the center of catalytic activity. , However, direct detecting the charge carrier dynamics on different crystal facets of a single crystal remains elusive. Most conventional approaches, such as transient absorption spectroscopy, electrochemical impedance spectroscopy (EIS) and so on, can only detect the integrity and average of the catalysts but ignore the effects of heterostructures, crystal-facet effects, and interface defects on the catalytic performance. , Visualizing the carriers dynamics at different sites in an individual singe crystal is conducive to in-depth understanding of the photocatalytic process. Single-particle photoluminescence (PL) spectroscopy, which can detect the PL intensity and lifetime changes at different positions of single nanoparticle, provides the direct and delicate evidence for charge carrier migration and recombination . Moreover, further study on the mechanism of charge carrier transfer at the facet-selective heterojunction interfaces at the single-particle level is conducive to understanding the structure–activity relationship.…”
Section: Introductionmentioning
confidence: 99%